False Low-Risk Single Nucleotide Polymorphism–Based Noninvasive Prenatal Screening in Pentasomy 49,XXXXY - Manesha Putra; Melissa A. Hicks; Jacques S. Abramowicz (American Journal of Perinatology Reports, 2018)
Introduction Pentasomy 49,XXXXY is a sex chromosome anomaly difficult to be diagnosed prenatally. We describe a patient of pentasomy 49,XXXXY with false low-risk results using a noninvasive prenatal screening (NIPS). A 30-year-old G1P0 woman presented at 336/7 weeks, secondary to sonographic fetal anomalies. She had low-risk NIPS at 136/7 weeks. Anatomy survey showed bilateral clubfeet, clinodactyly of the left fifth digit, micropenis, and echogenic bowel. Cytogenetics analysis revealed pentasomy 49,XXXXY syndrome. We report third-trimester sonographic features of a fetus with pentasomy 49,XXXXY and the importance of thorough pre- and posttest counseling for NIPS.